The Inhalation Anesthetic Isoflurane Induces a Vicious Cycle of Apoptosis and Amyloid β-Protein Accumulation - Xie, Zhongcong (J Neurosci, 2007)
The anesthetic isoflurane has been reported to induce apoptosis and increase Aβ generation and aggregation. However, the molecular mechanism underlying these effects remains unknown. We therefore set out to assess whether the effects of isoflurane on apoptosis are linked to amyloid β-protein (Aβ) generation and aggregation. For this purpose, we assessed the effects of isoflurane on β-site amyloid β precursor protein (APP)-cleaving enzyme (BACE) and γ-secretase, the proteases responsible for Aβ generation. We also tested the effects of inhibitors of Aβ aggregation (iAβ5, a β-sheet breaker peptide; clioquinol, a copper–zinc chelator) on the ability of isoflurane to induce apoptosis. All of these studies were performed on naive human H4 neuroglioma cells as well as those overexpressing APP (H4-APP cells). Isoflurane increased the levels of BACE and γ-secretase and secreted Aβ in the H4-APP cells. Isoflurane-induced Aβ generation could be blocked by the broad-based caspase inhibitor Z-VAD. The Aβ aggregation inhibitors, iAβ5 and clioquinol, selectively attenuated caspase-3 activation induced by isoflurane. However, isoflurane was able to induce caspase-3 activation in the absence of any detectable alterations of Aβ generation in naive H4 cells. Finally, Aβ potentiated the isoflurane-induced caspase-3 activation in naive H4 cells. Collectively, these findings suggest that isoflurane can induce apoptosis, which, in turn, increases BACE and γ-secretase levels and Aβ secretion. Isoflurane also promotes Aβ aggregation. Accumulation of aggregated Aβ in the media can then promote apoptosis. The result is a vicious cycle of isoflurane-induced apoptosis, Aβ generation and aggregation, and additional rounds of apoptosis, leading to cell death.